Maqashid Syariah dalam Perspektif Ekonomi Islam: Konsep, Peran, dan Implementasi - Revasyah Adesty; Salsabila Azzahra; Siti Aisyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The concept of Maqashid Sharia is the main principle in Islamic law that aims to protect five important points of human life: religion, soul, mind, offspring and property In the field of Islamic economics this concept is very important in the development of economic policies and practices that prioritize justice and benefit. This study aims to explain the concept of Maqsad Sharia its strategic role in the Islamic economic system and its application in various economic instruments and practices today. This research uses the literature study method by reviewing various scientific literature books and journals that are connected. The research shows that the principle of Maqashid Sharia is not only an ethical basis but also a normative framework in economic decision-making which includes the development of Islamic financial products and the distribution of justice and fair fiscal policy. In practice, it reflects an attempt to achieve a balance between the interests of individuals and society while maintaining the stability of Islamic values in the economy.